The Role of Village Government in Maintaining Security Stability in Harefa Village, North Nias Regency - Foster Eddy Elvis Gulo; Fatiani Lase; Darisalim Telaumbanua (Edumaspul: Jurnal Pendidikan, 2023)
The study aims to find out the role of the village government inining stability in the village, why there are still cases of crime and how the government is dealing with crime in the Northern District of Harefa. The purpose of the descriptive approach is to describe the process of conducting research that begins with observation. The research instrument used in this study is the researcher himself using his cell phones as a tool to record all the conversations, the results of images as real evidence, and the notebook that serves to record conversations with data sources or informants. The data collection techniques used are interviews, observations, and documentation. The results of the research and discussions concluded that: First, the role of the government of Harefa village inining the stability of the security of the village is to establish a good relationship of cooperation with the security authorities and the village people, the village government as a facilitator to resolve the crime cases that occurred, the three government of village sanctions for the perpetrators of crimes are either customary sanctions or government sanctions. And the four heads of village as the leader in the village will try their best to create security for the people. And the third effort of the village government in dealing with crime cases is to start from itself to create security, the second to socialize about order and security, and the third village government will provide aid to the people.